Non-classical B Cell Memory of Allergic IgE Responses - Saunders, Sean P.; Ma, Erica G. M.; Aranda, Carlos J.; Curotto de Lafaille, Maria A. (Frontiers in Immunology, 2019)
The long-term effectiveness of antibody responses relies on the development of humoral immune memory. Humoral immunity is maintained by long-lived plasma cells that secrete antigen-specific antibodies, and memory B cells that rapidly respond to antigen re-exposure by generating new plasma cells and memory B cells. Developing effective immunological memory is essential for the protection against pathogens, and is the basis of successful vaccinations IgE responses have evolved for protection against helminth parasites infections and against toxins, but IgE is also a potent mediator of allergic diseases. There has been a dramatic increase in the incidence of allergic disease in recent decades and this has provided the impetus to study the nature of IgE antibody responses. As will be discussed in depth in this review, the IgE memory response has unique features that distinguish it from classical B cell memory.